1991
DOI: 10.1039/c39910000062
|View full text |Cite
|
Sign up to set email alerts
|

Molecular recognition of anionic substrates. Binding of carboxylates by a macrobicyclic coreceptor and crystal structure of its supramolecular cryptate with the terephthalate dianion

Abstract: The macrobicyclic polyammonium receptor molecule 1-6H+ binds dicarboxylate substrates with linear recognition and forms with terephthalate a very stable dianion cryptate the crystal structure of which has been determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 10 publications
2
47
0
Order By: Relevance
“…The highest inclusion affinity was observed for terephthalate (logK = 4.4) whereas no particular selectivity was noted in the case of À OOC-(CH 2 ) n -COO À anions, for which logK values ranged from 3.1 to 3.4 upon moving from n = 2 to n = 7. [28] This lack of selectivity may be attributed to the higher flexibility of the spacers (an sp 3 carbon atom joins the two phenyl rings) and to the nondirectional character of the electrostatic interactions.…”
Section: Methodsmentioning
confidence: 99%
“…The highest inclusion affinity was observed for terephthalate (logK = 4.4) whereas no particular selectivity was noted in the case of À OOC-(CH 2 ) n -COO À anions, for which logK values ranged from 3.1 to 3.4 upon moving from n = 2 to n = 7. [28] This lack of selectivity may be attributed to the higher flexibility of the spacers (an sp 3 carbon atom joins the two phenyl rings) and to the nondirectional character of the electrostatic interactions.…”
Section: Methodsmentioning
confidence: 99%
“…For comparative purposes, Fig. 38 reports the log K values for the inclusion equilibria of linear aliphatic dicarboxylates by the hexaprotonated form of the bistren derivative 22 [76]. No selectivity is observed on varying the number of -CH 2 -groups present in the dianion from two to eight.…”
Section: (B) Imentioning
confidence: 94%
“…In particular it is observed that the most stable inclusion complex [75]. Hydrogen atoms of the cryptand and the four NO 3 À counterions have been omitted for clarity (diamonds, pH ¼ 7) [75], and by the hexaprotonated bistren receptor 22H 6 6+ (circles, pH ¼ 6) [76] Living in a Cage Is a Restricted Privilegecomplexes (aqueous solution, buffered at pH ¼ 7, 25 C) are formed with dicarboxylates with spacers consisting of n ¼ 3 (glutarate) and n ¼ 4 -CH 2 -groups (adipate), whose length seem to encompass quite well the Cu II -Cu II distance in the relaxed dimetallic receptor. Encapsulation of dicarboxylates with a shorter (n ¼ 2, succinate) and longer (n ¼ 5, pimelate) spacer probably induces drastic conformational rearrangements, which are reflected in a substantial decrease of the thermodynamic stability of the corresponding complexes.…”
Section: (B) Imentioning
confidence: 98%
“…4e6 Polyammonium cryptands have been successfully used in the recognition of inorganic anions, such as halogenates, nitrate, sulfate, phosphate, perchlorate, and short chain carboxylate anions like acetate, oxalate and malonate. 7e15 The recognition of aromatic carboxylate anions by this type of receptors is still scarce and the work of Lehn et al 7 is one of the rare reports in which an aromatic dicarboxylate anion, the terephthalate, is shown inserted into the polyammonium cryptand cavity. In fact, macrocycles are the mostly used receptors for binding of carboxylate anions.…”
Section: Introductionmentioning
confidence: 99%